Emmanuel Levinas: Reasons for an «a-theistic» metaphysic?: A reading of «Totality and Infinity» - Espigares, Pablo (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
On the occasion of the 50th anniversary of the publication ofTotality and Infinity , and conceived as a tribute, this paper presents Emmanuel Lévinas’ philosophical proposal as an «a-theistic» metaphysic on the transcendent alterity that, in opposition to any form of «philosophy of the neutral», develops to an ethical recreation of the subjectivity which avoids the excesses of the modern cogito . We will hold that, by inheriting a prophetic and demythologized eschatology, Lévinas is able to keep a critical distance to ontology and theology. Such a legacy makes possible to assume the testimony of an originary responsibility that Lévinas sets as the principle of individuation of the I. From that responsibility we may reinterpret the idea of God as something inseparable from the justice to which I am summoned by the Other.
Keywords: metaphysics; ethics; alterity; atheism; God